2014
DOI: 10.1037/neu0000001
|View full text |Cite
|
Sign up to set email alerts
|

The NIH Toolbox Cognition Battery: Results from a large normative developmental sample (PING).

Abstract: Objective The NIH Toolbox Cognition Battery (NTCB) was designed to provide a brief, efficient computerized test of key neuropsychological functions appropriate for use in children as young as 3 years of age. This report describes the performance of a large group of typically developing children and adolescents and examines the impact of age and sociocultural variables on test performance. Method The NTCB was administered to a sample of 1020 typically developing males and females ranging in age from 3 to 20 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
206
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 186 publications
(216 citation statements)
references
References 42 publications
8
206
1
1
Order By: Relevance
“…A validation of the Flanker Test with a pediatric population resulted in convergent validity of just .34 when compared with the D‐KEFS Inhibition test, and also found significant practice effects from repeated testing (Zelazo et al, 2013). Further, Akshoomoff et al (2014) found significant ceiling effects in older children when conducting a large normative study on the cognition battery. Unfortunately, the use of the NIH Cognition Toolbox does not facilitate strong conclusions about the efficacy of the ThinkRx program on selective attention.…”
Section: Discussionmentioning
confidence: 99%
“…A validation of the Flanker Test with a pediatric population resulted in convergent validity of just .34 when compared with the D‐KEFS Inhibition test, and also found significant practice effects from repeated testing (Zelazo et al, 2013). Further, Akshoomoff et al (2014) found significant ceiling effects in older children when conducting a large normative study on the cognition battery. Unfortunately, the use of the NIH Cognition Toolbox does not facilitate strong conclusions about the efficacy of the ThinkRx program on selective attention.…”
Section: Discussionmentioning
confidence: 99%
“…Details on the recruitment, ascertainment, behavioral, genetic, and neuroimaging methods and acquisition in the PING Study are summarized below (details are in refs. [43][44][45][46]. All participants provided informed consent (age 18 y old and older) or parental informed consent with child assent (ages 7-17 y old) in accordance with policies of the Institutional Review Boards of the sites of participation.…”
Section: Methodsmentioning
confidence: 99%
“…We utilized data from the PING (Pediatric Imaging, Neurocognition, and Genetics; (Akshoomoff et al, 2014)) dataset. PING is a neuroscientific dataset based on a large sample (n = 1,493) of healthy American children and youths, ages 3 to 21, of diverse ancestries.…”
Section: Data and Coding Of Variablesmentioning
confidence: 99%
“…The cognitive sub-domain assessed by each test, along with the subtests' psychometric characteristics, are detailed by Akshoomoff et al (2014) Some data were missing (5% of cells, 16% of cases had at least 1 missing datapoint). We imputed values for cases that were missing less than half of their datapoints rounded down (3 or fewer).…”
Section: Cognitive Datamentioning
confidence: 99%
See 1 more Smart Citation